A Phase I Study of the Hsp90 Inhibitor AUY922 plus Capecitabine for the Treatment of Patients with Advanced Solid Tumors. (26th November 2015) - Bendell, Johanna C.; Jones, Suzanne F.; Hart, Lowell; Pant, Shubham; Moyhuddin, Adil; Lane, Cassie M.; Earwood, Chris; Murphy, Patrick; Patton, Jeffrey; Penley, William C.; Thompson, Dana; Infante, Jeffrey R.
Abstract : Background : This phase I study determined the maximum tolerated dose (MTD) of AUY922 with capecitabine in advanced solid tumors. Methods : Capecitabine 1000mg/m 2 PO BID was administered with escalating doses of AUY922 IV; the MTD of AUY922 was combined with capecitabine 1250 mg/m 2 (DL6). Results : 23 patients were treated at 5 dose levels (22 mg/m 2 –70 mg/m 2 ). No DLTs were observed until DL6 (grade 3 diarrhea). Reversible vision darkening was seen in 26%. Four patients had partial response; 2 previously progressed on fluorouracil. Eight patients had stable disease (median 25.5 weeks). Conclusion : AUY922 plus capecitabine was well-tolerated up to 70mg/m 2 with encouraging preliminary efficacy.